Transformations of Library Science in the Digital Age: Challenges and Opportunities - BELABAS Abdelhamid (Ziglôbitha, 2024)
Abstract : The digital revolution has catalyzed profound shifts within the realm of library science, presenting both challenges and opportunities for the field. This article explores the multifaceted transformations occurring in library science amidst the advent of the digital age. It delves into the challenges stemming from the exponential growth of digital information, including issues of information overload, digital preservation, and equitable access. Additionally, it examines the opportunities afforded by digital technologies for libraries to innovate and redefine their roles in contemporary society. Through a comprehensive literature review and analysis of case studies, this article elucidates key challenges such as information management complexities and intellectual property rights concerns, while also showcasing examples of innovative practices and successful adaptation strategies. By addressing these challenges and capitalizing on opportunities, libraries can position themselves as dynamic centers of knowledge dissemination, digital literacy promotion, and community engagement. This abstract offers insights into the dynamic nature of library science in the digital age, underscoring the imperative for ongoing adaptation and innovation within the field. Keywords : Library Science, Digital Age, Transformations, Digital Technologies